Treatment for Mild Chronic Hypertension During Pregnancy. Issue 11 (November 2022) - Tita, Alan T.; Szychowski, Jeff M.; Boggess, Kim; Dugoff, Lorraine; Sibai, Baha; Lawrence, Kirsten; Hughes, Brenna L.; Bell, Joseph; Aagaard, Kjersti; Edwards, Rodney K.; Gibson, Kelly; Haas, David M.; et al.
Abstract : (Abstracted from N Engl J Med 2022;386:1781–1792) Chronic hypertension affects >2% of pregnancies in the United States and disproportionately affects Black women. The condition is also associated with an increased risk of adverse neonatal outcomes, including preeclampsia, placental abruption, preterm birth, small for gestational age (SGA), or perinatal death, and maternal outcomes, including maternal death, heart failure, stroke, pulmonary edema, or acute kidney injury.